(3MGTjI Ydi PcQ CUd GdQLhY hGdGSJbGeI aj (B" (3GdJPcQI (B"s - (3ceGd GdOjf GdMSf Hf Ydj Hf GdMSjf (B( (3GdMSf (B) (3GdaGQSis; (3GdfUjQ GdWhSj , eMeO Hf eMeO GdWhSj, fUjQ GdOjf CHh LYaQ,J (B672 (3g` s
(3ChdgG (B:s
(3bGd QFjS GdMceGA , SdWGf GdegfOSjf ceGd GdMSf Hf Ydi MGTjI Ydi PcQ CUd GdQLhY hGdESJbGeI ai GdJPcQI GdNW GdeSJbje GdehGLg ai GdZGHI s
(3BNQgG (B:s
(3hJHjf ef Pdc GdfXQ ai bhdg CNjQkG hEf LYd MQcJi , GdehGab ddeQcR hGdNGQL ddeQcR , eNGdaJjf ai GdLgI , Edi bhdg JHGOdJ MGdI GdbWYJjf GdbQjHJjf hGdHYjOJjf gPG eG MVQ ai GdHMK , hGddg CYde JeJ GdMGTjI s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH(B2s
(3HgG fXGe GdJYbjHIs
(3HgG CTcGds
(3cJHJ Hbde eged GdfbW CMjGfkGs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B30 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B11 - (3U (B207s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B3 - (3bSe (B2 s
Keywords: (3Gdadcs